2020
DOI: 10.3390/f11060697
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Preferences for Conservation and Breeding Programs of Forestry Food Resources in Niger

Abstract: In a less-favored area such as the Sahel, promoting sustainable management, breeding, and conservation of forestry resources would result in improvements for agroforestry systems and food security. A contingent ranking exercise allowed us to estimate the preferences and the values given by the rural population to the attributes that would be comprised in a conservation program. The resulting preferred program is farmer-managed natural regeneration (FMNR) based on the species Adansonia digitata (baobab), with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…In Niger, farmers have chosen a baobab-based agroforestry programme that suits their livelihood needs for its potential to improve their household food security and income [74]. A study of seed germination to enhance the performance of seeds of A. digitata in Nigeria found that a soak in 98% sulphuric acid for an hour prior to sowing improved establishment [75].…”
Section: Domesticationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Niger, farmers have chosen a baobab-based agroforestry programme that suits their livelihood needs for its potential to improve their household food security and income [74]. A study of seed germination to enhance the performance of seeds of A. digitata in Nigeria found that a soak in 98% sulphuric acid for an hour prior to sowing improved establishment [75].…”
Section: Domesticationmentioning
confidence: 99%
“…To date, priority setting for the domestication of indigenous fruit trees in the region has been done mostly on three fronts: (i) climate change and habitat suitability, e.g., [124,160,400,413]; (ii) farmers' preferences and prioritisation (e.g., [74,118,129,211,285,286,405,406,414,415]); and (iii) combined literature review and prioritization schemes [416].…”
Section: Priority Setting For Domestication/commercializationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the jargon of choice modelling, such effects are called attributes, and each attribute can have different values, which are called levels. Following previous results by Agúndez et al (2016 andAgúndez et al 2020), we selected the attributes and levels (Table 2), and conducted an experimental design of the programs to be evaluated by the farmers. We follow a contingent ranking approach, where each respondent started by selecting her best and worst choices, and then she was asked to identify her preferred choice between the remaining two alternatives.…”
Section: The Stated Preferences Studymentioning
confidence: 99%
“…Niger presents different agroecological zones [Sahelian, Sudanese-Sahelian and North Sudanese zones according to Yobom (2020)], with clear differences in the production of food resources, both agricultural and forestry (Moussa et al, 2016). Moreover, it turns out that farmers perceive climate change and want to act (Matchi et al, 2019), and they are willing to participate in improving the woody component of their traditional food production systems (Agúndez et al, 2020). Subsistence farming and livestock production are practiced according to traditional techniques.…”
Section: Introductionmentioning
confidence: 99%